Fenomena Teknologi Virtual Digital Di Dunia Arsitektur Dalam Proses Perencanaan dan Desain Perancangan Arsitektur - Ibadi, Raden Mohamad Wisnu; Doloksaribu, Hendrik Poltak (Jurnal Lingkungan Karya Arsitektur, 2024)
In the architectural planning and design process, the use of virtual digital technology is a necessity in the world of architecture today. The digital virtual technology used in the architectural planning and design process in this scientific paper is virtual reality, augmented reality and artificial intelligence. This technology is a further development after the era of digital architectural drawings on computers with special programs such as AutoCAD, ArchiCAD and the like. The process of planning and designing two-dimensional designs using a drawing table machine and paper media in the past, can now be directly created and viewed in three dimensions on a computer screen or via virtual digital technology tools. This study aims to study the potential and influence of digital virtual technology using qualitative-descriptive research methods through literature study. With this study, it is hoped that it can become a reference in distinguishing between the three digital virtual technologies, selected and used according to user needs in the architecture planning and design process.